Non-calcined pencil lead

By adjusting the ratio of scaly substances and lumpy particles in the physical material of the pencil lead, the gloss is reduced, the problem of inaccurate color of colored pencil leads under different light sources and angles is solved, and the accurate display of line color and mechanical strength are achieved. improvement.

CN119343415APending Publication Date: 2025-01-21MITSUBISHI PENCIL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380042996.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2023-05-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing colored pencil cores can produce gloss at different light sources and angles, resulting in inaccurate lines of color, especially when shooting and displaying poor tone.

Method used

By limiting the proportion of scaly substances in the pencil lead material to less than 20% and using block particles (such as calcium carbonate, magnesium sulfate, aluminum hydroxide, etc.) to account for more than 80%, the visual reflectivity is reduced and suppresses The luster of the lines.

Benefits of technology

Observing the lines from any direction is not conspicuous, ensure that the coloring tone is consistent with the observation color, and increases the mechanical strength by adding cellulose fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343415A_ABST
    Figure CN119343415A_ABST
Patent Text Reader

Abstract

A non-calcined pencil lead containing wax that is solid at room temperature, a coloring material, a body material, a water-soluble resin, and cellulose fibers, the proportion of scaly substances in the body material being 20 mass% or less, and the proportion of bulk particles in the body material being 80 mass% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to non-calcined pencil leads. Background Art

[0002] Until now, the development of non-calcined pencil leads such as colored pencil leads has focused on improving the coloring of the lines, the writing conditions, and the strength of the tip of the lead. In addition, wax is usually used as the main material of colored pencil leads to give the lines a gloss. For example, in the case of colored pencils that can also be used for cosmetics as described in Japanese Patent Publication No. 2005-514463, there are concerns about the formulation and manufacturing method of color transfer.

[0003] On the other hand, Japanese Patent Application Laid-Open No. 52-41028 discloses a crayon to which calcium carbonate is added as a curing agent. Japanese Patent Application Laid-Open No. 57-153060 discloses a solid drawing material to which calcium carbonate, talc, and barium sulfate are added as physical materials. Furthermore, Japanese Patent Application Laid-Open No. 2008-45043 discloses a non-calcined pencil lead containing calcium carbonate, kaolin, talc, precipitated barium sulfate, mica, and potassium titanate whiskers as physical materials. Summary of the invention

[0004] Problem that the invention aims to solve

[0005] Japanese Patent Publication No. 2005-514463 states that the gloss of the line can be adjusted by the type of wax added to the colored pencil. However, there is no record of a formula that does not produce gloss at all. There is a problem that the glossy line will be seen as a different color tone from the actual color tone at the angle where the gloss is produced, and this is often realized when viewing works at exhibitions, etc. In recent years, homemade paintings drawn with pencils or colored pencils have been photographed with cameras such as smartphones and are usually published on SNS, etc. When shooting, if the angle between the light and the camera is not set properly, the line will glow, and it will also cause the color tone to not be well presented in the image.

[0006] Here, the graphite particles contained in the pencil lead are one of the factors that contribute to the gloss of the line. In addition, in conventional colored pencils, the body materials mixed in addition to waxes, especially talc, are in a thin flaky shape, and therefore reflect light depending on the angle with the light source, which contributes to the gloss.

[0007] An object of an embodiment of the present application is to provide a non-calcined pencil lead that does not make the gloss of the line noticeable when viewed from any direction and that produces a line with no difference in color between the applied color and the observed color.

[0008] Solutions for solving problems

[0009] The non-calcined pencil lead according to an embodiment of the present application is characterized in that it comprises: wax that is solid at room temperature, a coloring material, a body material, a water-soluble resin and cellulose fibers, the ratio of flaky substances in the body material is 20% by mass or less, and the ratio of blocky particles in the body material is 80% by mass or more.

[0010] Here, as the block particles, it is desirable to use at least one of the group consisting of calcium carbonate, magnesium sulfate, aluminum hydroxide, and magnesium carbonate.

[0011] It should be noted that the visual reflectivity of the aforementioned physical material is expected to be lower than 0.1, and the visual reflectivity is defined by the ratio of the intensity of the reflected light at 90° to the intensity of the incident light irradiated from an angle of 45° on a smooth surface produced by mixing the melted SmackWax with the physical material in a mass ratio of 1:1, contacting with a glass surface and solidifying.

[0012] Effects of the Invention

[0013] The embodiment of the present application is configured as described above, and therefore can provide a non-calcined pencil lead that does not show the gloss of the line when viewed from any direction and that produces a line with no difference in color between the applied color and the observed color. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a perspective view schematically showing the appearance of a non-calcined pencil lead according to an embodiment. DETAILED DESCRIPTION

[0015] The non-calcined pencil lead of the embodiment of the present application comprises: wax which is solid at room temperature, a coloring material, a body material, a water-soluble resin and cellulose fibers, wherein the ratio of the flaky substance in the body material is less than 20 mass %, and the ratio of the block particles in the body material is more than 80 mass %.

[0016] Here, the flaky substance refers to a mineral having a thin sheet shape with an aspect ratio of 2 or more, and examples thereof include talc, kaolin, mica, or boron nitride. The thickness of the flaky substance can be set to, for example, less than 5 μm. That is, the flaky substance as a physical material easily reflects light, and thus becomes the cause of the gloss of the line. In the non-calcined pencil lead of the embodiment of the present application, the ratio of the flaky substance in the physical material is 20% by mass or less, and the ratio of the blocky particles that are not easy to reflect light in the physical material is 80% by mass or more, and thus the gloss of the line is suppressed.

[0017] Here, it is desirable that no flaky substance is contained as a physical material, but if the proportion of the flaky substance in the physical material is below 20 mass %, the gloss of the line can be fully suppressed. It should be noted that, when no flaky substance is contained as a physical material, that is, when it is 0 mass %, it is desirable that the blocky particles account for the total amount of the physical material, that is, 100 mass %.

[0018] In addition, it is desirable that the aforementioned block particles as the physical material are at least one of the group consisting of calcium carbonate, magnesium sulfate, aluminum hydroxide and magnesium carbonate. Furthermore, the visual reflectivity of the aforementioned physical material is less than 0.1, and the visual reflectivity is defined by the ratio of the reflected light intensity at 90° to the incident light intensity irradiated from an angle of 45° on a smooth surface produced by mixing melted SmackWax with the physical material at a mass ratio of 1:1, contacting with a glass surface and solidifying.

[0019] Wax that is solid at room temperature refers to, for example, wax having a melting point of 45° C. or higher. For example, stearic acid glyceryl having a melting point of 61° C., paraffin wax 135F having a melting point of 57° C., microcrystalline wax having a melting point of 84° C., and rosin ester having a softening point of 76° C. can be used as the wax according to the embodiment of the present application. In addition, any wax classified as glycerol fatty acid ester and pentaerythritol fatty acid ester can be used as the wax according to the embodiment of the present application as long as the melting point is 45° C. or higher.

[0020] As coloring materials, pigments or dyes used in the coloring of common colored pencils can be used. As pigments, for example, graphite, titanium oxide, iron black, carbon black, Prussian blue, ultramarine, blue No. 1, red iron oxide, yellow iron oxide, chromium oxide, chromium hydroxide, zinc oxide, zirconium oxide, cobalt oxide, fish scale foil, bismuth oxychloride and mica titanium, azo organic pigments such as disazo yellow AAA and pyrazolone orange, phthalocyanine organic pigments such as phthalocyanine blue and phthalocyanine green, advanced organic pigments such as quinacridone red, dye pigments such as final colors, and fluorescent pigments can be cited. In addition, in addition to pigments, dyes such as blue No. 2, blue No. 404, red No. 2, red No. 3, red No. 102, red No. 104, red No. 105, red No. 106, DPP red, yellow No. 4, yellow No. 5 and green No. 3 can also be used, and they can be used alone or mixed with two or more.

[0021] The water-soluble resin is used as a binder, and water-soluble organic polymers such as sodium carboxymethylcellulose, ammonium carboxymethylcellulose, polyvinyl alcohol, and methylcellulose can be used.

[0022] Cellulose fibers are obtained by refining natural wood cellulose, and preferably have an average particle size of 100 μm or less. The uncalcined pencil lead of the present embodiment contains cellulose fibers to improve mechanical strength.

[0023] The non-calcined pencil lead of the present embodiment can be manufactured, for example, by the following manufacturing method. That is, an equal amount of water is added to a mixture of wax, coloring material, body material, water-soluble resin and cellulose fiber, mixed and dispersed in a kneader, and then the water content is adjusted while kneading in a twin-roll mill. The obtained mixture is pelletized and extruded in a single-screw extruder into a pencil lead of a desired thickness. The molded lead is then dried to remove water, thereby obtaining a Figure 1 The unfired pencil lead 10 shown has a core body 11 which is generally cylindrical in shape.

[0024] Since the content of the flaky substance that causes the gloss of the line drawn by the non-calcined pencil lead produced as described above is small in the body material, the gloss is not noticeable even when photographed at any camera angle, and the original color tone is well expressed in the photographed image. In addition, the reduction in mechanical strength caused by the large proportion of blocky particles in the body material is enhanced by the inclusion of cellulose fibers.

[0025] Example

[0026] (1) Physical materials

[0027] It was verified whether the visual reflectance of the bulk material changes depending on the mixing ratio of calcium carbonate, barium sulfate, aluminum hydroxide or magnesium carbonate as block particles and talc as a flaky substance as raw materials of the bulk material.

[0028] Calcium carbonate, barium sulfate, aluminum hydroxide and magnesium carbonate used had average particle sizes of 3.2 μm, 1 μm, 1.4 μm and 5 μm, respectively. The average particle size of talc as flakes was 10 μm.

[0029] As physical materials, calcium carbonate and talc are mixed in the mixing ratios shown in Formula 1-1 to Formula 1-7 in the following Table 1, barium sulfate and talc are mixed in the mixing ratios shown in Formula 2-1 to Formula 2-7 in the following Table 2, aluminum hydroxide and talc are mixed in the mixing ratios shown in Formula 3-1 to Formula 3-7 in the following Table 3, and magnesium carbonate and talc are mixed in the mixing ratios shown in Formula 4-1 to Formula 4-7 in the following Table 4.

[0030] Each compounded physical material is formed into a powder, mixed with the melted SmackWax at a mass ratio of 1:1, and then the melted mixed wax is poured into a glass dish, cooled and solidified, and formed into a pellet with a diameter of 20 mm and a thickness of 5 mm as a measurement sample. In this measurement sample, the smooth surface produced by contact with the glass surface is used as the measurement surface. The measurement sample is placed on the measurement surface, and the visual reflectance defined by the ratio of the incident light intensity at an angle of 45° to the reflected light intensity at 90° is measured using PD-7 (Konica Minolta, Inc.). The results are also shown in the following Tables 1 and 2.

[0031] [Table 1]

[0032]

[0033] [Table 2]

[0034]

[0035] [Table 3]

[0036]

[0037] [Table 4]

[0038]

[0039] As shown in Table 1 and Table 2, it is known that when the block particles mixed as the physical material are any of calcium carbonate, barium sulfate, aluminum hydroxide or magnesium carbonate, as long as the mixing ratio of talc is below 20 mass %, the visual reflectivity becomes lower than 0.1. Thus, from the viewpoint of suppressing the gloss of the lines, it is inferred that the ratio of talc as a flaky substance in the physical material is below 20 mass % and is suitable.

[0040] (2)Raw materials

[0041] The non-calcined pencil lead of each example and each comparative example had the following composition. Stearyl glyceryl (POEM V-200, RIKEN VITAMIN CO., LTD.) with a melting point of 61° C. and rosin ester with a softening point of 76° C. were used as the wax. Sodium carboxymethylcellulose (F10MC, Nippon Paper) was used as the water-soluble resin. Respectively, as a black coloring material, carbon black (MA-100, Mitsubishi Chemical) is used, as a blue coloring material, phthalocyanine blue (CHROMOFINEBlue HS-3, Dainichi Seika Industries) is used, as a red coloring material, permanent red (SEIKAFAST RED4R-4016, Dainichi Seika Industries) is used, and as a green coloring material, phthalocyanine green (CHROMOFINE GREEN 2GO, Dainichi Seika Industries) is used, and as a white coloring material for improving brightness, titanium dioxide (JR-701, Tayca) and lithopone (B311, ANHUI UNION TITANIUM ENTERPRISE) are used. As a physical material, calcium carbonate (PC calcium carbonate, Shiraishi Industry), barium sulfate (P-30, Takehara Chemical Industry), aluminum hydroxide (RH-30, Iwatani Industry), magnesium carbonate (MS-S, Shinjima Chemical Industry) and talc (HIMICRON, Takehara Chemical Industry) are used, or a combination of two or more thereof. As cellulose fiber, KC FLOCK W-50 (Nippon Paper) is used. As an auxiliary additive, basic magnesium sulfate (MOS-HIGE, Ube Material Industries, Ltd.) is used.

[0042] (2-1) Example 1

[0043] The composition of Example 1 as a blue colored pencil lead is as follows: 33 mass % of glyceryl stearate, 2 mass % of rosin ester, 4 mass % of sodium carboxymethyl cellulose, 10 mass % of phthalocyanine blue and 10 mass % of titanium dioxide as coloring materials, 36 mass % of barium sulfate as a base material, and 5 mass % of cellulose fibers.

[0044] (2-2) Example 2

[0045] The composition of Example 2 as a red colored pencil lead is as follows: 33 mass % of glyceryl stearate, 2 mass % of rosin ester, 4 mass % of sodium carboxymethyl cellulose, 10 mass % of permanent red and 10 mass % of titanium dioxide as coloring materials, 36 mass % of barium sulfate as a base material, and 5 mass % of cellulose fibers.

[0046] (2-3) Example 3

[0047] The composition of Example 3 as a green colored pencil lead is as follows: 33 mass % of glyceryl stearate, 2 mass % of rosin ester, 4 mass % of sodium carboxymethyl cellulose, 10 mass % of phthalocyanine green and 10 mass % of titanium dioxide as coloring materials, 36 mass % of barium sulfate as a base material, and 5 mass % of cellulose fibers.

[0048] (2-4) Embodiment 4

[0049] The composition of Example 4 as a black colored pencil lead is as follows: 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethyl cellulose, 15% by mass of carbon black as a coloring material, 41% by mass of calcium carbonate as a body material, and 5% by mass of cellulose fibers.

[0050] (2-5) Example 5

[0051] The composition of Example 5, which is a black colored pencil lead, is as follows: 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethyl cellulose, 15% by mass of carbon black as a coloring material, 36% by mass of calcium carbonate as a body material, 5% by mass of cellulose fibers, and 5% by mass of basic magnesium sulfate.

[0052] (2-6) Example 6

[0053] The composition of Example 6 as a black colored pencil lead is set as: 33 mass% of glyceryl stearate, 2 mass% of rosin ester, 4 mass% of sodium carboxymethyl cellulose, 15 mass% of carbon black as a coloring material, 33 mass% of barium sulfate as a body material, 8 mass% of cellulose fibers, and 5 mass% of basic magnesium sulfate.

[0054] (2-7) Example 7

[0055] The composition of Example 7 as a black colored pencil lead is set as: 33 mass% of glyceryl stearate, 2 mass% of rosin ester, 4 mass% of sodium carboxymethyl cellulose, 15 mass% of carbon black as a coloring material, 5 mass% of talc and 36 mass% of calcium carbonate as a body material, and 5 mass% of cellulose fiber.

[0056] (2-8) Example 8

[0057] The composition of Example 8, which is a blue colored pencil lead, is as follows: 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethyl cellulose, 10% by mass of phthalocyanine blue and 10% by mass of lithopone as coloring materials, 36% by mass of barium sulfate as a base material, and 5% by mass of cellulose fibers.

[0058] (2-9) Example 9

[0059] The composition of Example 9 as a black colored pencil lead is set as: 33 mass% of glyceryl stearate, 2 mass% of rosin ester, 4 mass% of sodium carboxymethyl cellulose, 15 mass% of carbon black as a coloring material, 38 mass% of aluminum hydroxide as a body material, and 8 mass% of cellulose fibers.

[0060] (2-10) Example 10

[0061] The composition of Example 10 as a black colored pencil lead is as follows: 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethyl cellulose, 15% by mass of carbon black as a coloring material, 38% by mass of magnesium carbonate as a body material, and 8% by mass of cellulose fibers.

[0062] (2-11) Comparative Example 1

[0063] The composition of Comparative Example 1, which is a black colored pencil lead, is as follows: 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethylcellulose, 15% by mass of carbon black as a coloring material, 10% by mass of talc and 31% by mass of calcium carbonate as a body material, and 5% by mass of cellulose fibers.

[0064] (2-12) Comparative Example 2

[0065] The composition of Comparative Example 2, which is a black colored pencil lead, is as follows: 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethylcellulose, 15% by mass of carbon black as a coloring material, 20% by mass of talc and 21% by mass of calcium carbonate as body materials, and 5% by mass of cellulose fibers.

[0066] (2-13) Comparative Example 3

[0067] The composition of Comparative Example 3, which is a black colored pencil lead, is 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethylcellulose, 15% by mass of carbon black as a coloring material, 41% by mass of talc as a body material, and 5% by mass of cellulose fibers.

[0068] (2-14) Comparative Example 4

[0069] The composition of Comparative Example 4, which is a black colored pencil lead, is 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethylcellulose, 15% by mass of carbon black as a coloring material, and 46% by mass of calcium carbonate as a body material.

[0070] (2-15) Comparative Example 5

[0071] The composition of Comparative Example 5, which is a blue colored pencil lead, is 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethylcellulose, 10% by mass of phthalocyanine blue and 10% by mass of titanium dioxide as coloring materials, and 41% by mass of talc as a body material.

[0072] (2-16) Comparative Example 6

[0073] The composition of Comparative Example 6, which is a red colored pencil lead, is 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethylcellulose, 10% by mass of permanent red and 10% by mass of titanium dioxide as coloring materials, and 41% by mass of talc as a body material.

[0074] (2-17) Comparative Example 7

[0075] The composition of Comparative Example 7, which is a green colored pencil lead, is 33% by mass of glyceryl stearate, 2% by mass of rosin ester, 4% by mass of sodium carboxymethylcellulose, 10% by mass of phthalocyanine green and 10% by mass of titanium dioxide as coloring materials, and 41% by mass of talc as a body material.

[0076] (3) Manufacture of non-calcined pencil leads

[0077] The same amount of water was added to the raw materials of Examples 1 to 10 and Comparative Examples 1 to 7, mixed in a kneader, and then the water content was adjusted while kneading in a two-roll mill. The mixture was pelletized and formed into thin strands using a single-screw extruder. Examples 1 to 3 and 8 and Comparative Examples 5 to 7 were dried at 45°C for 24 hours to remove water. On the other hand, Examples 4 to 7, Examples 9 and 10 and Comparative Examples 1 to 4 were dried at 50°C for 24 hours to remove water, thereby obtaining blue non-calcined pencil leads (Examples 1 and 8 and Comparative Example 5), red non-calcined pencil leads (Examples 2 and Comparative Example 6), green non-calcined pencil leads (Examples 3 and Comparative Example 7), and black non-calcined pencil leads (Examples 4 to 7, Examples 9 and 10 and Comparative Examples 1 to 4) with a diameter of 2.5 mm.

[0078] (4) Lines

[0079] The handwritten lines were prepared by the sample preparation method specified in 8.9a of JIS S 6006:2020. Specifically, a line drawing paper (weight per unit area 78.3 to 205 g / m2) was spread on a flat glass plate. 2 , whiteness 75% or more), and repeatedly hand-painted with a non-calcined pencil lead in the horizontal and vertical directions so that the paper surface is evenly covered, thereby preparing a measurement sample.

[0080] The mechanical lines were produced according to the A method specified in 8.7.2 of JIS S 6006: 2020. Specifically, a measurement sample was produced by spirally writing a groove pattern on a line drawing paper using a recording marking machine equipped with an unburned pencil lead under the following writing conditions.

[0081] Paper for drawing lines: Mass per unit area 128±5g / m 2 Drawing paper

[0082] Writing load: 3N

[0083] Writing speed: 3.0m / min

[0084] Line spacing: 0.5mm

[0085] Line drawing distance: 6±1m

[0086] Writing angle: 75°

[0087] Core tip shape: Cone shape with a taper angle of 17±1° and a tip diameter of 0.6±0.1mm

[0088] Core rotation: One rotation for each line drawn

[0089] (5) Brightness measurement

[0090] Brightness was measured as follows: For each Example and each Comparative Example, the handwritten lines and machine lines were measured using a chromaticity meter (SC-P, Suga Test Instruments Co., Ltd.).

[0091] (6) Gloss measurement

[0092] The gloss was measured as follows: That is, for each Example and each Comparative Example, the gloss at 60° and the gloss at 85° were measured for the handwritten lines and the machine lines, respectively, using a digital variable angle gloss meter UGV-5 (manufactured by Suga Test Instruments Co., Ltd.).

[0093] (7) Bending strength measurement

[0094] Ten unfired pencil leads of each of the above-mentioned examples and comparative examples were subjected to the bending strength test specified in 8.6 of JIS S6006:2020, and the average value was obtained. That is, a load of 10 mm / min was applied to the center of the unfired pencil lead supported at 60 mm between the fulcrums using a TENSILON universal material tester (RTC-1150A, Orientec), and the load (F, unit: N) when the unfired pencil lead was broken was measured, and the bending strength (σ, unit: MPa) was calculated using the following formula (1). It should be noted that the top end to which the load was applied and the top ends of the two fulcrums were in an arc shape, and the radius (R) was R = 0.2 ± 0.02 (mm).

[0095] σ=8Fl / πd 3 Formula (1)

[0096] It should be noted that "l" in the above formula (1) is the distance between the supporting points (mm), which is 60 mm in this case. In addition, "d" in the above formula is the diameter of the unfired pencil lead (mm), which is 2.5 mm in this case. The bending strength was measured immediately after production.

[0097] (8) Measurement results

[0098] The results of the brightness measurement, gloss measurement, and bending strength measurement of the above-mentioned Examples and Comparative Examples are shown in Table 5 below.

[0099] [Table 5]

[0100]

[0101] First, the examples 1 and 8 of the same color tone were compared with the comparative example 5, the example 2 and the comparative example 6, and the example 3 and the comparative example 7. In any of the examples, the ratio of barium sulfate as a blocky particle in the body material was 100 mass%, and in any of the comparative examples, the ratio of talc as a flaky substance in the body material was 100 mass%. In addition, in any of the comparative examples, the gloss value at 85° in the handwritten line was higher than 10, and in the comparative examples 5 and 7, the gloss value at 85° in the mechanical line was higher than 10. In contrast, in any of the examples, the gloss value measured under any condition was lower than 10. In addition, there was no significant difference in brightness between the examples and the comparative examples. From the above, it can be seen that in the colored non-calcined pencil lead, the flaky substance in the body material is replaced with blocky particles, so that the gloss is suppressed without affecting the brightness.

[0102] It should be noted that both Example 1 and Example 8 have the same blue color, but different titanium dioxide and lithopone are used as white pigments. However, there is no significant difference in any measurement results. It is inferred that lithopone can be used as a substitute for titanium dioxide as a white pigment.

[0103] Next, Examples 4 to 7, 9 and 10, and Comparative Examples 1 to 3, which are black non-calcined pencil leads, were examined. In all Examples, the ratio of calcium carbonate, barium sulfate, aluminum hydroxide or magnesium carbonate as blocky particles in the body material was 80% by mass or more, and in all Comparative Examples, the ratio of talc as a flaky substance in the body material was 20% by mass or more. That is, in Examples 4 to 6, 9 and 10, the ratio of talc in the body material was 0% by mass, and in Example 7, the ratio was 12.2% by mass (talc 5% by mass, calcium carbonate 36% by mass). In contrast, the ratio was 24.4% by mass (talc 10% by mass, calcium carbonate 31% by mass) in Comparative Example 1, 48.8% by mass (talc 20% by mass, calcium carbonate 21% by mass) in Comparative Example 2, and 100% by mass in Comparative Example 3.

[0104] Moreover, in Comparative Examples 1 to 3, the gloss values ​​at 85° in the mechanical lines were all higher than 10, and in Comparative Examples 2 and 3, the gloss values ​​at 85° in the handwritten lines were all higher than 10, and the gloss value at 60° in Comparative Example 3 was also higher than 10. In contrast, in Examples 4 to 7, Examples 9 and 10, the gloss values ​​measured under any conditions were also lower than 10. It should be noted that there is no clear difference in brightness between the Examples and the Comparative Examples. As can be seen from the above, in the non-calcined pencil lead as a black colored pencil lead, the scale-like substance in the body material is replaced with blocky particles, so that the gloss is also suppressed without affecting the brightness.

[0105] It should be noted that in Comparative Example 4, the ratio of calcium carbonate in the body material is 100% by mass, but cellulose fibers are not contained, so the bending strength is significantly reduced. It can be seen that the mechanical strength of the non-calcined pencil lead borne by talc as a body material is supplemented by cellulose fibers.

[0106] Industrial Applicability

[0107] The invention can be used as a non-calcined pencil lead.

Claims

1. A non-calcined pencil lead, comprising: a wax which is solid at room temperature, a coloring material, a body material, a water-soluble resin and cellulose fibers, The ratio of the flaky substances in the body material is 20 mass % or less, and the ratio of the block particles in the body material is 80 mass % or more.

2. The non-calcined pencil lead according to claim 1, wherein: The block particles are at least one of the group consisting of calcium carbonate, magnesium sulfate, aluminum hydroxide and magnesium carbonate.

3. The non-calcined pencil lead according to claim 1 or claim 2, wherein: The visual reflectivity of the physical material is less than 0.1, and the visual reflectivity is defined by the ratio of the intensity of reflected light at 90° to the intensity of incident light irradiated from an angle of 45° on a smooth surface produced by mixing melted SmackWax with the physical material in a mass ratio of 1:1, contacting with a glass surface and solidifying.

Citation Information

Patent Citations

  • Method of manufacturing crayon

    JP1977041028A

  • Solid drawing material

    JP1982153060A

  • Lipid-based gel material containing pigment

    JP2005514463A

  • Nonbaked lead for color pencil

    JP2008045043A